Influence of attitude, ethics, technology affordances and social wellbeing on using smartphones among Malaysian higher learning students - Landani, Zahra Mardani
The evolution of new mobile technologies such as smartphone not only has influenced the way people communicate, but has also shaped their attitudes and ethical behavior. The advent applications of smartphone which are accessible and user friendly have shifted the conventional teaching and learning towards innovative methods. Thus, smartphones are not only used for communicating, but also searching, sharing information and learning from each other, which leads to active participation in learning. In this study, the main investigation was designed to determine the trend of mobile usage among Malaysian higher learning students based on attitude, ethics, technology affordances, social wellbeing and their actual use in learning (m-learning). Secondly, the researcher attempted to study the influence of students' attitude, ethics, technology affordances and social wellbeing in using smartphones on m-learning. A model has been hypothesized based on a framework from theories related to Theory of Acceptance, Structuration Theory, Connectivism and Khan's e-learning framework. A total of 582 students responded from three research universities in Malaysia (UM, UTM, UPM) which were selected through proportional sampling. A mix method with the explanatory sequential design has been employed. An adapted questionnaire with 50 items was used based on a 5-point Likert scale in measuring students' experience from strongly agree to strongly disagree. Additionally, semi-structured interviews with four informants were conducted to collect qualitative data. These informants were selected purposively based on their experience in using smartphones in learning. Descriptive statistics and Stepwise Regression have been employed for the analysis procedures. To confirm the results, cross validation was employed. Even though high dependency on the technology is apparent, the findings reveal that the majority of students show positive attitude in using smartphone which is determined from the indicators to check notifications, reading and replying immediately and giving feedback in group messages when needed. From ethical standpoint, the students seem to show ethical use of smartphone from the indicators of switching off whenever they are in the mosque, church or temple and putting in silent mode while meeting the lecturers. Moreover, majority of the students have agreed that they do not have any technical problems accessing the internet using their smartphone applications while in campus that leads to positive technology affordances. The actual use of smartphone in learning has shown that students search more information during class. Additionally, the results of social wellbeing in using smartphones show that students are satisfied when they can retrieve information via smartphones. However, when these factors are hypothesized in a model with actual use as the dependent variable, it has been found that ethics is not able to determine the actual use of smartphone in m-learning. The findings have contributed to the literature of m-learning which related to the culture of learning to be imparted in the framework. This research has also addressed the empirical evidence to support m-learning and the theories tested.